Impact of Interaction Between Marketing Mix Elements on Retail Product Purchase Choices - Saiyed, Rahma; Hasan, Hanif; Lamsir, Seno; Firmansyah, Edy (ProBisnis : Jurnal Manajemen, 2025)
This decline in consumers has resulted in a decline in sales levels in the retail industry in Indonesia, where the growth in retail product sales in 2024 is 4%. The problems that arise in several retailers in Indonesia are the very low quality of local products in retail, lack of product differentiation, so that consumers find it difficult to get unique product models that match their desires and expectations, product layout in several retailers tends to be untidy and haphazard, and product promotions delivered have not been able to increase high customer growth, so that there are still many customers who decide not to use and buy a number of products in certain retailers in Indonesia. This study's objective is to understand and look at the impact among the four 4P variables and blend of marketing interaction variables between item of product and price, as well as price and promotion, on Indonesian consumers' choices regarding retail merchandise. Multiple regression analysis is used in the quantitative descriptive method of the study. Based on the research results, partially only the variables of product, price, distribution, promotion and product x price interaction variables influence the decision to purchase a product, where the price x promotion interaction variable does not influence the decision to purchase a retail product through consumers. Simultaneously, the variables of product, price, distribution, promotion, product x price interaction variables and price x promotion variables influence the decision to purchase a product.